2010
DOI: 10.1007/s10681-010-0226-8
|View full text |Cite
|
Sign up to set email alerts
|

A QTL controlling low temperature induced spikelet sterility at booting stage in rice

Abstract: Low temperature is a major abiotic stress for rice cultivation, causing serious yield loss in many countries. To identify QTL controlling low temperature induced spikelet sterility in rice, the progeny of F2, BC1F1 and BC2F1 populations derived from a Reiziq 9 Lijiangheigu cross were exposed to 21/15°C for 15 days at the booting stage, and spikelet sterility was assessed. For genotyping, 92 polymorphic markers from 373 SSR and 325 STS primer pairs were used. A major QTL was initially indentified on the short a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 20 publications
4
37
0
Order By: Relevance
“…This QTL explained 33% of the phenotypic variation in spikelet fertility and its additive effect (a = −10.5) was from WAB56-104. In a similar overlapping interval as qCTB-10 in this study, a major QTL for cold tolerance (qLTSPKST10.1) was identified on the short arm of chromosome 10 in a 3.5 cM interval which explained 20.5% of the phenotypic variation (Ye et al, 2010). Xu et al (2008) identified a QTL (qCTB-10-2) in another cross population in the same interval which explained 14.9% of the total phenotypic variance.…”
Section: Qtls Identified For the Agronomic Traits Under Normal Water supporting
confidence: 70%
“…This QTL explained 33% of the phenotypic variation in spikelet fertility and its additive effect (a = −10.5) was from WAB56-104. In a similar overlapping interval as qCTB-10 in this study, a major QTL for cold tolerance (qLTSPKST10.1) was identified on the short arm of chromosome 10 in a 3.5 cM interval which explained 20.5% of the phenotypic variation (Ye et al, 2010). Xu et al (2008) identified a QTL (qCTB-10-2) in another cross population in the same interval which explained 14.9% of the total phenotypic variance.…”
Section: Qtls Identified For the Agronomic Traits Under Normal Water supporting
confidence: 70%
“…Likewise, five SSRs distributed on chromosomes 8, 9, 10, and 12 were found associated with spikelet fertility under cool-air environment greenhouse. QTLs for cold tolerance at the booting and reproductive stages in rice were previously mapped on all of the chromosomes (Saito et al 2001;Andaya and Mackill 2003;Xu et al 2008;Suh et al 2010;Ye et al 2010). Spikelet fertility may be a critical factor associated with cold tolerance and yield under cold stress.…”
Section: Ssr Markers Associated With Spikelet Fertility Under Cold Stmentioning
confidence: 99%
“…Extensive genetic studies and QTL analysis with DNA markers have been conducted on several mapping populations. QTL analyses have recently revealed that there are numerous QTLs for cold tolerance in the rice genome (Saito et al 2001;Andaya and Mackill 2003;Xu et al 2008;Suh et al 2010;Ye et al 2010). The objectives of this study are to identify promising cold-tolerant rice cultivars and to characterize the genetic relationship among the coldtolerant japonica rice germplasm provided by the international partners of the TRRC.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic systems for conferring cool tolerance in rice are not clear, although many quantitative trait loci (QTLs) for cool tolerance at the booting stage have been detected (Takeuchi et al, 2001;Andaya and Mackill, 2003;Ye et al, 2010;Zhou et al, 2010;Kuroi et al, 2011). Saito and his colleagues (2001,2004,2010) have explored QTLs that correlated with cold tolerance of spikelet fertility at the booting stage in rice, and they indicated that an F-box protein gene, located on chromosome 4, is one of the genes conferring cold tolerance based on results from map-based cloning.…”
Section: Introductionmentioning
confidence: 99%